Problem solving for learning disabilities in Malaysian Muslim Blind community - Asmilyia Mohd Mokhtar; Ahmad Yunus Mohd Noor; Dahlila Putri Dahnil Sikumbang (Penerbit Universiti Kebangsaan Malaysia, 2022)
Issues which are consist in learning disability context for the blind comprises several aspects such as; teachers did not teach the Quran by using the Quran in braille, have not mastered in Quran Braille code, have not basic learning on the Quran and alphabetical character. This article attempts to find out the issues and challenges of learning disabilities experienced by Muslim Blind Community in Malaysia. The study also aims to solve problems on learning disabilities among Muslim blind community in Malaysia by using braille approach. This study undertakes an analysis of people with learning disabilities based on issues and challenges as the main sources of reference by adopting the document analysis method. Therefore, this study used a qualitative method with a protocol of observation and analysis of several sources to get data and information. The outcome of this article suggests that the Malaysia government needs to make improvements in order to enhance the quality of education for people with learning disabilities and create a special education program for them. This paper clarifies that the methods and point solutions to the problems faced by this kind of people is considered as a new issue and supposed to be handled by government and private sector.